(untitled) (International Journal of Nursing Education, 2020)
This research explores the differences in test results and the use of some generic skills in the Problem-BasedLearning (PBL) model and the Lecture-Based Learning (LBL) model. This research was conducted with amixed research method, namely quantitative method and qualitative method. The researcher implementedthe two models in two different classes, the control class (N = 28) and the experimental class (N = 72).Both learning method successfully activate the use of self-directed learning skills, teamwork skills, criticalthinking skills, and problem-solving skills. However, PBL is better in motivating and increasing awarenessabout lectures so there is a better use of these skills in lectures. Students are very challenged to solve clinicalproblems relevant to the nursing profession with their group of friends. This in turn has an impact on thehigher test results obtained by the experimental class than the control class. Therefore, researchers suggestapplying it widely in all nursing majors.